Impact of Inoculant Sources on Feed in Vitro Fermentability and Digestibility : Dampak Cairan Rumen Sumber Inokulan pada Fermentabilitas dan Kecernaan Pakan secara In Vitro - A K Agustina A K Agustina; D Evvyernie; Rika Zahera; I G Permana; Toto Toharmat; S Suryahadi; D Despal (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2020)
The aim of this research is to compare alternative inoculant source for in vitro rumen fermentation. In the first experiment, inoculant from fistulated cattle kept in LIPI and IPB (Fis1 and Fis2) and inoculant from Bogor municipality abattoir and IPB abattoir (Abo1 and Abo2) were tested for their pH, total bacterial count, and protozoal number using a complete block design with four replications. In the second experiment, the effect of the inoculant sources was tested on cornmeal (F1), soybean oil meal (F2), Napier grass (F3), and dairy cattle complete ration (F4) fermentability and digestibility including pH, VFA, NH3, IVDMD and IVOMD parameters. The results showed an unsignificant different protozoal number among inoculant sources. The pH of Fis2 rumen liquor was significantly lower (p<0.05) than others. The bacterial population was significantly higher (p<0.05) in Fis2 and Abo2 than Abo1, and Fis1. The inoculant pH after feed fermentability was not influenced by feed type but inoculant source with Fis1 was significantly higher (p<0.05) than Fis2, Abo2, and Abo1. The ammonia, VFA concentration, IVDMD, and IVOMD were influenced by interaction between inoculant sources and feed types. Although inoculant from cattle close to the laboratory (Fis2 and Abo2) were better in term of higher bacterial population, higher fermentability and digestibility for most type of feeds but other sources can be used in vitro study without differences in average fermentability and digestibility results. Key words: abattoir, fermentability, fistula, inoculant, in vitro